The Representation of Toxic Masculinity in the "Do Revenge" Movie - Aldi Pramudiya; Erwin Oktoma; Yuniarti Yuniarti (Journey: Journal of English Language and Pedagogy, 2023)
Toxic masculinity is a social condition created by society in which men can't express their feelings, and they shouldn't cry and be weak otherwise, they will be violating the norm, that's because they can't express their feelings; they use violence, emphasizes power, discrimination against gender in general. Netflix's movie entitled Do Revenge present an american teenager with some problems in their life, and it presents the character that represents the behavior of toxic masculinity named Max Broussard. This study used the theory of toxic masculinity by Kupers (2001) to identify how Max's character represents toxic masculinity in the movie. The qualitative method with a case study approach was the primary methodology of this research. The researcher gathered the data by watching the movie, reviewing earlier studies, and concentrating on the language and the scene that addressed either direct or indirect toxic masculinity issues. Previous research has not specifically classified various forms of toxic masculinity, such as misogyny, greed, homophobia, and violent domination, within the context of character behavior in the movie. Therefore, the novelty of this research lies in the more detailed classification of the forms of toxic masculinity that emerge in the character of Max in the movie "Do Revenge". The results of the study showed that the character represents toxic masculinity in the movie with 13 scenes and 15 dialogue data in the form of misogyny with the criteria hatred towards women, aggressive, likes to organize women, greed with the motive of sex, and violent domination with the category control, intimidation, and bullying